Kepercayaan Khurafat Tentang Saidina Ali di Kalangan Masyarakat Melayu di Malaysia - Senik, Mohd Yusoff (Jurnal Usuluddin, 1995)
This article exposes tales among the Malay society that involve Syaidina Ali bin Abi Talib as a super human being. For example, some Malays believe that Ali was very strong man, if he stamped his foot onto the earth, it will scream and tremble. The tale also tells Ali’s sword Zulfiqar, if thrown into the sea, the silent sea will turn into rolling waves.